Atomic and laser spectroscopy - Corney, Alan.; Oxford eBooks (Oxford : Clarendon, 1977)
Discusses advances in optical physics and is intended for experimentalists. This book introduces the interaction of electromagnetic radiation with free atoms using classical or semi-classical calculations wherever possible. Topics discussed include the spontaneous emission of radiation, and atomic beam magnetic resonance experiments.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Atomic spectroscopy; Laser spectroscopy; Electronic books